The butterfly defect : how globalization creates systemic risks, and what to do about it - Goldin, Ian, 1955-; Mariathasan, Mike, 1982- (Princeton : Princeton Univ Press, 2015)
"Global hyperconnectivity and increased system integration have led to vast benefits, including worldwide growth in incomes, education, innovation, and technology. But rapid globalization has also created concerns because the repercussions of local events now cascade over national borders and the fallout of financial meltdowns and environmental disasters affects everyone. The Butterfly Defect addresses the widening gap between systemic risks and their effective management. It shows how the new dynamics of turbo-charged globalization has the potential and power to destabilize our societies. Drawing on the latest insights from a wide variety of disciplines, Ian Goldin and Mike Mariathasan provide practical guidance for how governments, businesses, and individuals can better manage risk in our contemporary world. Goldin and Mariathasan assert that the current complexities of globalization will not be sustainable as surprises become more frequent and have widespread impacts. The recent financial crisis exemplifies the new form of systemic risk that will characterize the coming decades, and the authors provide the first framework for understanding how such risk will function in the twenty-first century. Goldin and Mariathasan demonstrate that systemic risk issues are now endemic everywhere--in supply chains, pandemics, infrastructure, ecology and climate change, economics, and politics. Unless we are better able to address these concerns, they will lead to greater protectionism, xenophobia, nationalism, and, inevitably, deglobalization, rising conflict, and slower growth. The Butterfly Defect shows that mitigating uncertainty and systemic risk in an interconnected world is an essential task for our future"--
Includes bibliographical references and index.
Keywords: Crisis management; Globalization; Risk management; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / International / General; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Globalization; Print books